Functional Outcomes in Older Patients Following Patella Fracture Repair - Contractor, Amaya M.; Konda, Sanjit R.; Leucht, Philipp; Ganta, Abhishek; Egol, Kenneth A. (The Journal of Knee Surgery, 2025)
The purpose of this study is to examine the effect of age on outcomes following repair of acute displaced patella fractures. A total of 248 patients who sustained a displaced patella fracture and underwent open reduction and internal fixation were identified. Patients included underwent a similar operative protocol, were prescribed a standard postoperative protocol of therapy, and were seen at standard follow-up intervals. Patients were divided into groups of <65 years old (young) and ≥65 years old (older). Statistical analysis was run to determine if there was a significant difference in range of knee motion and rate of major complications. Of the 248 patients, 149 were young and 99 were older. The mean age of the old group was 74.5 ± 6.7 and the mean age of the young group was 50 ± 12. Fracture pattern and BMI were the same across the groups. However, the old group had a higher average Charlson Comorbitiy Index (CCI) (p < 0.001). Additionally, the groups had similar length of follow-up (p = 0.693) and similar mean time to radiographic healing (p = 0.533). Older patients had limited knee extension at 6 months compared with young patients (p = 0.031). Finally, old patients had a higher rate of all complications compared with young patients. About 2% of old patients developed a fracture-related infection (FRI), 4% developed a symptomatic nonunion, and 11% were underwent reoperation including removal of hardware, total knee replacement, irrigation and debridement, and manipulation under anesthesia. Complication rates following patella fracture fixation in older patients were worse than young patients, despite having similar injury patterns, surgical treatment, and follow-up. These findings can better inform treating physicians during surgical intervention of older patients with patella fractures.
Keywords: patella; trauma mechanism; knee fracture